Application of integrated local plant species and vesicular basalt rock for the treatment of chromium in tannery wastewater in a horizontal subsurface flow wetland system. Issue 4 (August 2020) - Alemu, Agegnehu; Gabbiye, Nigus; Lemma, Brook
Abstract: In this study, integrated local plant species and vesicular basalt were used in the constructed units with a horizontal subsurface flow wetland system to investigate the removal efficiency of chromium in tannery wastewater. Four pilot units were vegetated with Pennisetum purpureum, Typha domingensis, Cyprus latifolius, and Echinochloa pyramidalis, and a fifth unit was left unvegetated (control). The constructed wetland units vegetated with P. purpureum and C. latifolius were effective in removing chromium up to 99.38 % and 99.21 % respectively in the 6 days of hydraulic retention time. All the constructed wetland units were effective in removing chromium from the tannery wastewater and there was no statistically significant difference between the vegetated and control units. The plant species used for removal of Cr (III) indicated bioconcentration factor >1 and translocation factor <1. Based on its rapid growth and biomass production, P. purpureum can accumulate more Cr (III) in its above-ground parts compared to the other three plant species. The integrated horizontal subsurface flow wetland units indicated high treatment potential of chromium (III) in the tannery wastewater, which is below the standard discharge limit set to surface water bodies (2 mg L −1 ) according to Ethiopia EPA.